Не дают мне покоя номархи… - Мурзин, В.Ю. (Археологія і давня історія України, 2019)
В очередной раз в данной статье мы вынуждены обратиться к нашему пониманию места номархов
в социальной структуре скифской военно-политической организации и критериям выделения погребальных сооружений номархов из общего массива
скифских погребальных памятников. This article is a kind of response to the work of
T. M. Kuznetsova, in which she argues that a reliable
indicator of the burials of Scythian «kings» and nomarhs
is the presence of bronze boilers in the grave goods.
We are still confident that quite definitely we can
select from the total mass of Scythian burials only the
tombs of the supreme «kings» of Scythia (and not so
much by the presence of boilers, but by other signs) and
the burials of ordinary Scythians. It is impossible to isolate the burials of the Scythian
«younger kings» and nomarchs from a significant array of funerary monuments of the highest Scythian aristocracy,
including by the presence of boilers. This is explained by the fact that the social and property
status of the nomarchs, depending on the number of soldiers in his nome, as well as the nobility of this
unit of the Scythian horde, were very different. All the foregoing applies to younger kings as well. Moreover,
the nomarch, who was at the head of one of the nomes (tribes) of the Scythians-royals, could surpass
the «younger king», who led the least privileged wing («kingdom») of the Scythian nomadic community.
And if we consider that the highest Scythian aristocracy could include military leaders, who became famous not for
their nobility, but for military victories, as well as assistants to the supreme king (in the current language — advisors),
who had management experience, and others whose functions we can only guess, the picture that emerges is
quite variegated, so we hardly ever succeed to understand it, due to the limitedness of our knowledge.